PREDICTION OF STRENGTH PROPERTIES OF SELF CURING CONCRETE BY REGRESSION ANALYSIS - Dr. S. S. Kadam,; S. Kumar, (The Bioscan, 2025)
For achievement of strength to concrete curing process performs crucial role. Nowadays infrastructure development is not possible without concrete. In region where scarcity of water there is problem of curing with water and it affects strength and durability of concrete. Therefore, in present investigation natural and chemical admixtures were added in concrete which helps to cure concrete without external water. Curing admixture such as Polyethylene glycol 400 [PEG 400] and wood powder [WP] used in percentage of 1%, 1.5%, 2% and 6%, 7%, 8% respectively. It was observed that concrete achieves considerable strength for combination of 1.5% PEG400 and 8% wood powder. The experimental outcomes are validated with regression techniques. Strength of concrete predicted by regression equations which helps to reduce time and money for preparation of concrete.